The Importance of Indigenous Technical Knowledge and Geographical Information Systems (GIS) in Sustainable Natural Resource Management around the Teso Community in Kenya - Dominics Dan Ayaa; John Kapoi Kipterer (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
There is a growing awareness on the importance of indigenous technical knowledge and the necessity of its integration into modern knowledge in order to address problems related to natural resource conservation. However, there is a lack of study that demonstrates clearly how the two types of knowledge systems could be successfully integrated together. This paper presents such a framework that has been developed through a participatory geographical information systems (GIS) approach with the Teso Community in Kenya. Data were collected using a variety of research instruments such as structured questionnaires, in-depth and face-to-face interviews, focussed group discussions, content analysis of literature, environmental check lists, and using the GIS techniques for assessing the status of the bio-physical environment. The process of developing such a framework comprises five key building blocks including stakeholder engagement, establishment of resources targeted for rehabilitation, establishment of community and scientific points of convergence and divergence, a decision on community and expert resolutions and the adoption of community-based project implementation, monitoring and evaluation. The study recommends that the developed framework could be easily replicated in other rural communities that have similar bio-physical environmental conditions if found successful in sustainably managing natural resources. The local community members will through the guidance of the elders use their indigenous knowledge to map out and analyze the natural resources targeted for conservation to ascertain the extent of degradation.